Using the Central Mosque Coordinates of the Regency or City for Calculations of Prayer Times in the Province of Jambi - Tasnim Rahman Fitra (Al-Marshad: Jurnal Astronomi Islam dan Ilmu-Ilmu Berkaitan, 2023)
This article describes the application of the coordinates of the district/city central mosque in determining the prayer time schedule in Jambi Province. The use of the coordinates of the central mosque in determining the prayer time schedule raises indications of problems if applied to areas with large stretches of territory.  This research is a field research with analytical descriptive analysis method. The data obtained is processed through a comparison of prayer time schedules in 11 districts / cities in Jambi province between the calculation base of the central mosque and the calculation base of the westernmost point of the area concerned. The results of this study indicate that the coordinates of the central mosque of the regency / city are used as the basis for calculating the prayer time schedule on the grounds that these mosques are considered representative and represent their respective regions. However, the application of the coordinates of the central mosque has an impact on not covering some areas with a maximum value of 1 minute 52 seconds. This is convincing evidence (qarinah) with the implication of having to make corrections to the use of the markaz of the central mosque of the district/city in the calculation of the prayer time schedule in Jambi province.